2020
DOI: 10.1080/21655979.2020.1860492
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA (lncRNA) PGM5P4-AS1 inhibits lung cancer progression by up-regulating leucine zipper tumor suppressor (LZTS3) through sponging microRNA miR-1275

Abstract: It is necessary to explore new molecules for the improvement of precise diagnosis and antitumor therapies in lung cancer. LncRNAs (long non-coding RNAs) play an important role in the regulation of cancer cell malignant behavior and tumor development. In this work, we found that a newly discovered lncRNA, lncRNA PGM5P4-AS1, was lower expressed in lung cancer tissues than adjacent tissues. Then, the lncRNA PGM5P4-AS1 was overexpressed or knocked-down in different lung cancer cells, and its effects on the maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The wild-type HOXA-AS3 containing the miR-218-5p seed sequence fragment (HOXA-AS3 Wt) and mutant-type (HOXA-AS3 Mut) luciferase vectors were conducted. The luciferase reporter assay was conducted as previously reported [ 7 ]. The OSCC cells (5 × 10 3 cells) were seeded into 48-well plates and were co-transfected with the luciferase vectors and miR-218-5p mimics or negative control using Lipofectamine® 2000 Reagent for 48 h. This assay was normalized with 0.05 μg of the RFP expression vector pDsRed2-N1 (Clontech, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wild-type HOXA-AS3 containing the miR-218-5p seed sequence fragment (HOXA-AS3 Wt) and mutant-type (HOXA-AS3 Mut) luciferase vectors were conducted. The luciferase reporter assay was conducted as previously reported [ 7 ]. The OSCC cells (5 × 10 3 cells) were seeded into 48-well plates and were co-transfected with the luciferase vectors and miR-218-5p mimics or negative control using Lipofectamine® 2000 Reagent for 48 h. This assay was normalized with 0.05 μg of the RFP expression vector pDsRed2-N1 (Clontech, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of studies have recently demonstrated that aberrant expression of lncRNAs play vital roles in many different types of human cancer, including OSCC, osteosarcoma, hepatocellular carcinoma, nasopharyngeal carcinoma, and gastric cancer [ 6 ]. LncRNAs are associated with the biological characteristics of malignant tumors, such as oncogenesis, development, and metastasis [ 7 , 8 ]. Increasing evidence has demonstrated the important roles of lncRNAs in regulating the biological performances of OSCC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the cells reached 70% confluence, the diameter through the plate was drawn using a sterile pipette, and the floating cells were washed away. At 0 and 24 h, images of the scratches were obtained using a light microscope and recorded [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that lncRNAs aberrant expression is closely related to the progression of numerous types of cancer ( 6 , 7 , 21 ), suggesting that lncRNAs might be involved in the progression of cancer. In addition, numerous lncRNAs, including PTAR ( 22 ), NBR2 ( 23 ) and DLEU2 ( 24 ), have been reported to be abnormally expressed in NSCLC.…”
Section: Discussionmentioning
confidence: 99%